Analisis Sebaran Konversi Lahan Pertanian di Kecamatan Muara Bangkahulu Kota Bengkulu - Yurike Yurike; Ayub Sugara; Anitya Dwi Putri (University of Jember, 2023)
This study aims to determine the pattern of land use change and the pattern of distribution of land conversion that occurred in Muara Bangkahulu District in the period 2010-2022. This study uses a quantitative method with a spatial analysis approach that utilizes Geographic Information System technology and surveys to conduct ground checks in the field on the interpretation of land conversion results from satellite imagery data. The analysis used is nearest neighbor analysis and descriptive analysis. The results showed that there were only two patterns of land change that occurred in Muara Bangkahulu District, namely oil palm plantation areas turning into residential areas and agricultural areas turning into residential areas. The high rate of change of land use into residential areas is due to the subsidized housing program in Muara Bangkahulu District. The pattern of distribution of land conversion that occurs can be seen through the pattern of distribution of settlements in Muara Bangkahulu District which is included in the random category with a value of T = 1.064934 meaning that land conversion occurs in each village and the change tends to be permanent because it has changed its function to become built-up land or settlements.